IMPLEMENTASI PENDEKATAN TEACHING AT THE RIGHT LEVEL (TARL) KELAS 3 SEKOLAH DASAR NEGERI NGUTER 04 SUKOHARJO - Yaya Dimas Andika; Dwi Anggraeni Siwi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to describe the implementation of the Teaching at the Right Level (TaRL) approach in the learning process of third-grade students at Nguter 04 Public Elementary School in Sukoharjo. TaRL is a learning approach that focuses on identifying and addressing students’ learning needs based on their actual ability levels, rather than their age or grade level. This approach is essential for addressing learning achievement gaps at the primary level, particularly in reading and arithmetic skills. This research employs a qualitative method with a descriptive approach. The research subjects include third-grade teachers, the school principal, and third-grade students. Data collection techniques involve observation, in-depth interviews, and documentation. Data analysis follows the interactive model by Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results of the study show that the implementation of the TaRL approach in the third grade at SDN Nguter 04 involves several stages: initial diagnostic assessment, grouping students based on ability levels, and conducting differentiated instruction tailored to each group’s needs. The teacher demonstrated a good understanding of TaRL principles and was able to adjust teaching strategies according to the actual classroom conditions. However, there are still challenges in the implementation, such as limited time, the need for further teacher training, and inadequate learning facilities.